Perbandingan Penggunaan Nail Polish dan Nail Gel pada Hasil Jadi Nail Art dengan Tema Rasi Bintang - Tias, Ayu Ning; Maspiyah, Maspiyah (Journal of Beauty and Cosmetology (JBC), 2020)
Nail is a part of the body that could support women to beautify themselves. Characteristics of a healthy and normal nail are strong, springy, have a pinkish color, smooth surface, curved clean without any holes and waves at the edges. Nail art is the art of decorating nails to make them look more beautiful. The purpose of this study was to determine the result comparison of nail art with the theme of constellations using nail polish and nail gel, which included 1) conformity to the design, 2) the flatness of nail art results, 3) neatness and 4) panelist favorite level. This type of research is experimental research (True Experimental Design). Data collection method using the methods of observation, carried out using instruments in the form of a checklist. The panelist of this study were 30 people. The data analysis technique used in this research is descriptive quantitative. The result showed that the comparison between nail polish and nail gel, 1) conformity to design, the results of nail polish scored 3.4 and nail gel 3.7. 2)  Flatness, the nail polish result obtained a value of 3.43 and nail gel 3.6. 3) Neatness, the result of nail polish gained 3.43 and nail gel 3.63. 4) The panelists favorite level, the nail polish results obtained a value of 3.5 and nail gel 3.6.Keywords: Nail Polish, Nail Gel, Nail Art.